Proceedings of the First Workshop on Argumentation Mining 2014
DOI: 10.3115/v1/w14-2111
|View full text |Cite
|
Sign up to set email alerts
|

Mining Arguments From 19th Century Philosophical Texts Using Topic Based Modelling

Abstract: In this paper we look at the manual analysis of arguments and how this compares to the current state of automatic argument analysis. These considerations are used to develop a new approach combining a machine learning algorithm to extract propositions from text, with a topic model to determine argument structure. The results of this method are compared to a manual analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…As Lawrence et al [26] suggested, the presence of topic-relevant words and phrases in a sentence is a good indicator of the sentence being a candidate.…”
Section: Semi-supervised Argument Component Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Lawrence et al [26] suggested, the presence of topic-relevant words and phrases in a sentence is a good indicator of the sentence being a candidate.…”
Section: Semi-supervised Argument Component Detectionmentioning
confidence: 99%
“…The annotators were experts in computational linguistics and are of age between[25][26][27][28][29][30][31][32][33][34][35] years.…”
mentioning
confidence: 99%
“…Previous work employs rule-based identification (Persing and Ng, 2016), featurebased classification (Lawrence et al, 2014), conditional random fields (Sardianos et al, 2015;Stab, 2017), or deep neural networks (Eger et al, 2017). Especially the most recent approaches by Stab and Eger et al rely on sophisticated structural, syntactical, and lexical features.…”
Section: Related Workmentioning
confidence: 99%
“…In Lawrence et al (2014), LDA is used to decide whether a proposition can be attached to its previous proposition in order to identify non directional relations among propositions detected through classifiers based on words and part-ofspeech tags. LDA has been also used to mine lexicons of argument (words that are topic independent) and domain words (Nguyen and Litman, 2015), by post-processing document topics generated by LDA.…”
Section: Related Workmentioning
confidence: 99%